Railway pantograph-catenary interaction performance in an overlap section: Modelling, validation and analysis. (31st March 2023) - Song, Yang; Rønnquist, Anders; Jiang, Tengjiao; Nåvik, Petter
Highlights: The measurement data is used to validate the pantograph-catenary model in overlap sections. Strong dependence on interaction performance of the speed with crossing point height is observed. Steady arm damper improves the trailing pantograph's performance but sacrifice the leading one's. Abstract: The overlap section is a railway catenary arrangement where the pantograph transfers from one section to another. In the overlap section, the unsynchronised vibration of two contact wires, contact wire height variation, and elasticity unevenness destabilise the pantograph-interaction performance. This paper presents a systematic investigation of the dynamic behaviours of the pantograph-catenary in an overlap section, including the mathematical modeling, model validation and numerical analysis. In combination with the traditional shape-finding method, an initialization procedure is proposed to accurately describe the crossing point height in an overlap section of a catenary. The measurement data of the maximum uplift of the crossing point collected from the field test in the Gardemobanen line is utilised to validate the pantograph-catenary model in the overlap section. The numerical analysis mainly focuses on the effect of the crossing point height and the inclusion of steady arm damping on the interaction performance at different speeds. The results indicate a strong dependence of the dynamic behaviour in an overlap section on the train speed. A good performance can be achieved with a low crossing point when the speed is much lower than the design speed, while a high crossing point can benefit the transition distance and maximum contact force at high speed. The inclusion of a steady arm damper can improve the pantographs' performance at a low speed. However, the effectiveness degrades with the increase of the train speed, especially for the leading pantograph.